The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1515/pz-2021-2012
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphised warlike beings with horned helmets: Bronze Age Scandinavia, Sardinia, and Iberia compared

Abstract: Horned-helmet imagery continues to raise questions about what is local and what is global in Bronze Age Europe. How similar is the imagery found on Sardinia, in southwestern Iberia and southern Scandinavia in material appearance, medium of representation, and sociocultural setting? Does it occur at the same point in time? Does it spring from or transmit a shared idea? Analysis reveals intriguing patterns of similarity and difference between the three zones of horned-helmet imagery 1000–750 BC. The results poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this context of involvement of local communities in long-distance connections, also attested by artefacts that can be related to other areas of Europe and the Mediterranean (Harrison 2004), it is not surprising to find warrior iconographies in interior regions which are depicting motifs and compositions that are broadly shared, not only within Iberia but also beyond, as far away as the Aegean or Nordic Europe (Vandkilde et al 2022). But, as the case studies illustrate, as well as local communities' involvement in the extraction and circulation of metals (Senna-Martínez et al 2011), and probably other resources, they were actively involved in the appropriation and reinterpretation of ideas and objects that had broad circulation (Vilaça 2013: 22), such as the warrior archetype and related gear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context of involvement of local communities in long-distance connections, also attested by artefacts that can be related to other areas of Europe and the Mediterranean (Harrison 2004), it is not surprising to find warrior iconographies in interior regions which are depicting motifs and compositions that are broadly shared, not only within Iberia but also beyond, as far away as the Aegean or Nordic Europe (Vandkilde et al 2022). But, as the case studies illustrate, as well as local communities' involvement in the extraction and circulation of metals (Senna-Martínez et al 2011), and probably other resources, they were actively involved in the appropriation and reinterpretation of ideas and objects that had broad circulation (Vilaça 2013: 22), such as the warrior archetype and related gear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lead isotope and chemical analysis of Scandinavian and British bronzes indicated that copper with an isotopic signature matching southern Iberian ores (most probably the Alcudia valley and the Ossa Morena region) was used to manufacture artefacts from around 1400 BC (Period II, 1500-1300 BC), but more intensely in Periods IV and V (1100-700 BC) including swords and shields (Ling et al : 121-129, 2019. Thus, we must therefore consider an Atlantic route that connected the terminus zones of Atlantic Europe, Iberia and Scandinavia (Ling & Uhnér 2014) in addition to the aforementioned 'amber route' (see also Vandkilde et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation